Analysis of Factors Causing Delays in Outpatient Medical Record Returns at Puskesmas Ajung - Rahmadanti, Ainun Safira; Swari, Selvia Juwita; Nuraini, Novita; Vestine, Veronika (P3M Politeknik Negeri Jember, 2025)
The rate of late returns of outpatient medical records at the Ajung Jember Health Center increased from 5.36% in July 2022–April 2023 to 20.07% in January–February 2024. Several factors are believed to contribute to these delays, including inadequate staff qualifications, the absence of rewards and punishments, suboptimal training, and ineffective implementation of standard operating procedures (SOPs). This study analyzes these delay factors using McCormick and Tiffin's performance theory, which considers both individual and situational factors. A qualitative research method was applied, with research subjects including the head of the puskesmas, registration officers, and other medical personnel. Data were collected through interviews, observations, and brainstorming sessions, and analyzed using data collection, data reduction, data presentation, and drawing conclusions. The results indicated that individual factors included the educational background of medical record officers and suboptimal application of punishment. Situational factors included a lack of training, inadequate SOP implementation, and ineffective expedition forms. It is expected that Puskesmas Ajung will conduct socialization with the officers involved in the return process, optimize the application of punishment, provide training related to medical record management (especially for staff involved in the return process), review the SOP, and add a borrowing date column as a monitoring tool.